(untitled) (Research, Society and Development, 2022)
Objective: Execute a literature review and describe the related factors of overweight children and teenagers with Autism Spectrum Disorder (ASD). Methodology: The study consists of an integrative review, made through a MEDLINE/Pubmed database search. Original papers, non-experimental, with people under 20 years old from both genders and described diagnosis criteria for overweight and ASD, which had data of factors related to overweight in ASD people and free online access were included. There weren’t any restrictions on language or publication year. Results: 486 papers were initially identified, and after exclusions, considering eligibility criteria, totaled 20 papers included in this review. The prevalence of overweight varied between 27,5% and 63,8%. Among the related factors of overweight found stood out: higher age among the pediatric population with ASD, black race, Hispanic/Latin ethnic groups, lower parent scholarity, parental body mass index, elevated body mass at birth, genetic, sleep or affective disorders, antipsychotic drugs and humor stabilizers use, low daily life adaptive ability, motor competence loss, selectivity, low food refusal and/or reward, higher meal numbers and lower physical activity level. Conclusion: The frequency of overweight in pediatric people with ASD was elevated, having multiple related factors, being the main aspects related to socio-demographics, genetics, clinic factors, dietary habits, comorbidity presence from ASD, drugs, low physical activity, and ASD-related characteristics.